DISIPLIN LALU LINTAS PENGENDARA SEPEDA MOTOR RODA DUA DI KECAMATAN TAMPAN PEKANBARU - Nur Hidayah; Basri " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Disciplines on traffic for two-wheel motorcycle riders in Pekanbaru Handsomedistricts where many violations of traffic violations that occur for two-wheeled motorcyclespengandaradikecamatan Handsome, offenses committed while the rider is the completenessof the vehicle, completeness letter mail, Hlem, against the current , breaking signs, speedlimits above the maximum, no lights menayalakandising day. There is also the formulation ofthe problem in this study is the first 1 What characteristics of the people who violate trafficrules for riders of two-wheeled motorcycle in the District Handsome Pekanbaru. 2 Whatfactors cause people are not disciplined in riding a two-wheeled motorcycle in PekanbaruHandsome districts.The theory used in this study is the theory of aberration, kepeda I am here using thetheory of aberration. Because any traffic violations for motorcyclists is called aberration, hereis deviant behavior is any behavior that constitutes a violation of the norms of a group orcommunity.Data collection techniques used herein the first form of observation, the authorsconducted research directly in the field to obtain the necessary data in the study, both in theform of a questionnaire that question in the questionnaire can be in the form of closedquestions (structured). The question is if the structure of the questionnaire has been availableabout the possible answers. Data collection techniques will be carried out in this study byusing in-depth interview techniques is by using questionnaires.The results show respondents are not discipline-causing factors in driving a twowheeledmotorcycle in Pekanbaru Handsome districts seen from the characteristics ofrespondents who violate terms of age, from the age of 15-30 years, by gender of most men,education level of the respondents in violation of junior high school to university, Triberespondents who violate the Minang, religion professed by respondents who violate theIslamic religion. views of the respondents did not factor causes traffic discipline in theabsence of a sense of concern for others, are not concerned with the safety of both for himselfand the safety of others, lack of discipline of the respondents in traffic, especially for ridersof two-wheeled motorcycles. The magnitude of the influence of the local environment.Keywords: Traffic Discipline, riders of two-wheeled motorcycles